2016
DOI: 10.1016/j.neuron.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-type Guanylyl Cyclases Confer Thermosensory Responses in C. elegans

Abstract: SUMMARY Thermosensation is critical for optimal regulation of physiology and behavior. C. elegans acclimates to its cultivation temperature (Tc), and exhibits thermosensitive behaviors at temperatures relative to Tc. These behaviors are mediated primarily by the AFD sensory neurons which are extraordinarily thermosensitive, and respond to thermal fluctuations at temperatures above a Tc-determined threshold. Although cGMP signaling is necessary for thermotransduction, the thermosensors in AFD are unknown. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(119 citation statements)
references
References 41 publications
3
116
0
Order By: Relevance
“…(Figure S4C). Consistently, the heat-induced redistribution of ELC-2 occurs in mutants that are defective in thermosensory response of the major thermosensory neurons AFD (Mori and Ohshima, 1995, Takeishi et al, 2016) (Figure S4D), indicating that ELC-2 responds to the noxious heat independent of the canonical thermosensory circuit. While it is still possible that other non-autonomous signals, such as electrical communication, may trigger nuclear enrichment, these results raise the interesting possibility that the ADF sensory neurons are capable of directly sensing noxious heat.…”
Section: Resultssupporting
confidence: 57%
“…(Figure S4C). Consistently, the heat-induced redistribution of ELC-2 occurs in mutants that are defective in thermosensory response of the major thermosensory neurons AFD (Mori and Ohshima, 1995, Takeishi et al, 2016) (Figure S4D), indicating that ELC-2 responds to the noxious heat independent of the canonical thermosensory circuit. While it is still possible that other non-autonomous signals, such as electrical communication, may trigger nuclear enrichment, these results raise the interesting possibility that the ADF sensory neurons are capable of directly sensing noxious heat.…”
Section: Resultssupporting
confidence: 57%
“…Thermotaxis begins when temperature-sensitive GCYs produce cGMP in the AFD dendrite (38). cGMP binds and activates TAX-2/TAX-4, which mediates Ca 2ϩ influx and depolarization (25,(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…AFD neurons are the principal thermosensory cells of the C. elegans nervous system (25). In AFD, temperature-regulated guanylate cyclases (GCYs) catalyze synthesis of cGMP (38), which binds and allosterically activates TAX-2/TAX-4 channels. Thermal signals are ultimately transmitted to interneurons (for processing and integration) and associated motor neurons that guide migration and isothermal tracking behavior (25).…”
Section: Pkc-2 Links Thermosensory Signals To Learned Behaviormentioning
confidence: 99%
“…Recent studies have elucidated physiological roles of rGCs in C. elegans , on which we focus in this review. Ectopic expression of rGCs in different neurons has shown that rGCs play roles as direct sensor molecules for alkaline pH, molecular CO 2 , and temperature in sensory neurons (2628). Many other rGCs are also involved in salt gustation, olfaction, pheromone detection, phototransduction, and body-size regulation.…”
Section: Introductionmentioning
confidence: 99%